2021
DOI: 10.1002/adfm.202102524
|View full text |Cite
|
Sign up to set email alerts
|

2D Layered Dipeptide Crystals for Piezoelectric Applications

Abstract: 2D piezoelectric materials such as transition metal dichalcogenides are attracting significant attention because they offer various benefits over bulk piezoelectrics. In this work, the fabrication of layered biomolecular crystals of diphenylalanine (FF) obtained via a co‐assembly of l,l‐ and d,d‐ enantiomers of FF monomers is reported. Their crystal structure, thermal and chemical stabilities, and piezoelectric properties are investigated. Single crystal X‐ray diffraction results show that FF enantiomers are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 94 publications
(106 reference statements)
0
14
0
Order By: Relevance
“…Low-frequency piezoresponse force microscopy (PFM) study in contact mode (corresponding force–distance curves are given in Figure S7 ) of the powders of compounds 3a and 3b transferred to aluminum foil revealed that the average amplitude of the piezo signal from photodetector was much higher in the case of compound 3a as compared with compound 3b ( Figure 3 ) (full experimental details are given in Materials and Methods section and references therein [ 19 , 20 ]). Conversion of the vertical PFM signal values into the d 33 coefficient provided the average values of 2.74 ± 0.54 (compound 3a ) and 0.57 ± 0.11 pm/V (compound 3b ).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Low-frequency piezoresponse force microscopy (PFM) study in contact mode (corresponding force–distance curves are given in Figure S7 ) of the powders of compounds 3a and 3b transferred to aluminum foil revealed that the average amplitude of the piezo signal from photodetector was much higher in the case of compound 3a as compared with compound 3b ( Figure 3 ) (full experimental details are given in Materials and Methods section and references therein [ 19 , 20 ]). Conversion of the vertical PFM signal values into the d 33 coefficient provided the average values of 2.74 ± 0.54 (compound 3a ) and 0.57 ± 0.11 pm/V (compound 3b ).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…If no dielectric anomaly is observed in this regime, the compound can be considered piezoelectric or pyroelectric rather than ferroelectric. 20,21 Among the array of valence tautomeric compounds reported so far, the pyroelectric properties reported by Sato and coworkers can be observed in the absence of an electric field because the molecular orientation in the molecular crystals is fixed. 18,19 Moreover, the advanced design strategy can improve the predictability and precision during the incorporation of polar molecular crystals into energy-efficient materials.…”
Section: Discussionmentioning
confidence: 99%
“…If no dielectric anomaly is observed in this regime, the compound can be considered piezoelectric or pyroelectric rather than ferroelectric. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…Among the LD piezoelectric materials, many of them show piezoelectric effects in both bulk and their LD counterparts. These materials included both layered and nonlayered structures. The bulk form with the piezoelectric feature has been widely adopted in sensors, actuators, and many other microsystems.…”
Section: Pristine Ld Materials With Intrinsic Piezoelectricitymentioning
confidence: 99%